2004
DOI: 10.1182/blood-2004-03-0826
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib and pegylated human recombinant interferon-α2b in early chronic-phase chronic myeloid leukemia

Abstract: for the GIMEMA Working Party on Chronic Myeloid Leukemia Since interferon-␣ and imatinib (IM; STI571, Glivec, Gleevec) are effective for the treatment of chronic myeloid leukemia (CML), and their mechanisms of action are different, we designed an exploratory study investigating the effects of a standard IM dose (400 mg/d) and a variable pegylated interferon-␣ (PegIFN) dose (50 g/wk, 100 g/ wk, and 150 g/wk). The criteria for dose adjustment were designed so as to ensure the delivery of the IM dose and to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 51 publications
(46 reference statements)
0
47
0
Order By: Relevance
“…Phase 2 studies have been recently conducted with preliminary interesting results. 26,27 Improvement of tolerance and efficacy with pegylated formulation of IFN-␣ is another promising approach. 27 The potential beneficial effect of IFN-␣ or Ara-C combined with imatinib is being evaluated in large phase 3 trials.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2 studies have been recently conducted with preliminary interesting results. 26,27 Improvement of tolerance and efficacy with pegylated formulation of IFN-␣ is another promising approach. 27 The potential beneficial effect of IFN-␣ or Ara-C combined with imatinib is being evaluated in large phase 3 trials.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of the included articles is given in Online Supplementary Table S3. 14,15, Only 19 peer review articles were analyzed and reported in the Results section.Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.27 Almost half of the included studies were retrospective (9 of 19) and mainly conducted in the US and Asia 38,41,42,45,49,52,53 while half of the European studies were prospective (4 of 8). 14,15,18,24 …”
mentioning
confidence: 99%
“…Seventy-six patients were treated with the combination of imatinib 400 mg/daily and PegIFNα, at doses ranging from 50μg to 150 μg weekly, 16 while 419 patients were treated with imatinib 400 mg/daily alone. Patients' characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] All patients gave written informed consent to the studies which were approved by the Ethics Committee of each participating institution and conducted according to the principles of the Helsinki declaration. Briefly, cytogenetic analysis was performed by standard chromosome banding analysis of marrow metaphases and cytogenetic response was rated according to the European LeukemiaNet guidelines.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation